Promoviendo geografías deportivas feministas: La inserción del baloncesto femenino en el paisaje cultural de Puerto Rico - Díaz Torres, Rafael (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This paper focuses on the field of sports geography in the context of Puerto Rico and its women’s basketball National Team. Information is provided about the moments of both struggles and accomplishments in which Puerto Rican basketball players from different times were involved. This paper also analyzes the claims that both female basketball players and sports feminism activists have made in support of gender equity in Puerto Rican sports. Public support for women basketball players is presented through two cases in which feminist activists have advocated for the development of new Puerto Rican sports geographies that integrate the voices, experiences and identities of women athletes.